2015
DOI: 10.1152/ajpheart.00267.2015
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of cyclooxygenase attenuates the blood pressure response to plantar flexion exercise in peripheral arterial disease

Abstract: Muller MD, Drew RC, Ross AJ, Blaha CA, Cauffman AE, Kaufman MP, Sinoway LI. Inhibition of cyclooxygenase attenuates the blood pressure response to plantar flexion exercise in peripheral arterial disease. Am J Physiol Heart Circ Physiol 309: H523-H528, 2015. First published June 8, 2015 doi:10.1152/ajpheart.00267.2015.-Prostanoids are produced during skeletal muscle contraction and subsequently stimulate muscle afferent nerves, thereby contributing to the exercise pressor reflex. Humans with peripheral arteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
20
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 40 publications
7
20
1
Order By: Relevance
“…With respect to BP and HR, the current plantar flexion experiments are consistent with previous studies from our laboratory, which found that systolic BP and HR responses to plantar flexion exercise up to 2.0kg were augmented in PAD [15, 26, 34]. The primary finding of the current study, which used a longer exercise protocol, is that ΔCBV from baseline to exercise is attenuated in PAD despite higher myocardial metabolism (RPP).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…With respect to BP and HR, the current plantar flexion experiments are consistent with previous studies from our laboratory, which found that systolic BP and HR responses to plantar flexion exercise up to 2.0kg were augmented in PAD [15, 26, 34]. The primary finding of the current study, which used a longer exercise protocol, is that ΔCBV from baseline to exercise is attenuated in PAD despite higher myocardial metabolism (RPP).…”
Section: Discussionsupporting
confidence: 90%
“…The resistance started at 0.5 kg and increased by 0.5 kg every minute until 7 kg, fatigue, significant pain, or inability to maintain the cadence occurred as previously performed in our lab [15, 26, 27]. Ratings of perceived exertion and pain were obtained each minute using the Borg scales [28].…”
Section: Methodsmentioning
confidence: 99%
“…For Protocol 1, repeated measures ANOVA was used to determine the effect of exercise workload on HR, MAP, and popliteal velocity over time. Planned paired t-tests were conducted at 1, 2, 3, and 4 min of exercise (using the last 20 sec of each minute) based on our previous publications with single-leg plantar flexion exercise (Muller et al 2012(Muller et al , 2015Drew et al 2013). For Protocol 2, mean data from all 400 scans were plotted and paired t-tests were conducted at 1, 2, 3, and 4 min of exercise.…”
Section: Discussionmentioning
confidence: 99%
“…Planned paired t ‐tests were conducted at 1, 2, 3, and 4 min of exercise (using the last 20 sec of each minute) based on our previous publications with single‐leg plantar flexion exercise (Muller et al. , ; Drew et al. ).…”
Section: Methodsmentioning
confidence: 99%
“…However, despite slower onset kinetics, the magnitude of skeletal muscle desaturation is augmented during graded submaximal and fatiguing work in PAD (Luck et al, ). This indicates that O 2 utilization increases relative to O 2 supply, reflecting an elevated metabolic perturbation which likely contributes to the exaggerated exercise pressor reflex observed in these patients (Miller et al, ; Muller et al, ; Ross et al, ).…”
Section: Introductionmentioning
confidence: 94%